Theologising the discourse of representation through ‘faith’ and religion in football news - Nadhratunnaim Abas; Surinderpal Kaur (Penerbit Universiti Kebangsaan Malaysia, 2019)
The paper examines the use of ‘faith’ in football through the analysis of the patterns of its co-occurrences in the corpus of football news articles in The Star, a local Malaysian English language newspaper. These articles have been produced by the local news authors who claim to be the faithful of particular football teams. The use of ‘faith’ has been found to express and call for the allegiance towards the preferred teams which is addressed to the audience in general. In this sense, the overdetermined role of the authors as the news producers and the supporters of certain football teams may contribute to how they are represented in the media. Moreover, ‘faith’ has often been limited to religion and little is known about its use in sport and representation. Hencethe investigation is aimed at making sense of the meanings of ‘faith’ in the context of football to further unveil its role in the discourse of representation. The results reveal the co-occurrences of ‘faith’ with the vocabulary of religion simulating interdiscursive relations that strategise on theologising the representation of the news participants in attempts to legitimise the allegiance to particular sides in football naturally. Consequently, using faith of religion to call for faith in football may lead to the glorification and derogation of certain football teams that further influence their representation as ‘Us’ or ‘Them’. As this practice may also be accepted as a common practice indicating sports rivalry, it also makes ‘faith’ a naturalised code without appearing to be ideological.